2011
DOI: 10.1002/marc.201000806
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Conductivity of Polyaniline by Conjugated Crosslinking

Abstract: A novel crosslinked conductive polyaniline (PANI) was prepared by chemically copolymerizing aniline (An) and p-phenylenediamine (PPDA) with triphenylamine (TPA) as crosslinker, using ammonium peroxydisulfate (APS) as an oxidant. The effects of different preparation conditions on the electrical conductivity of polymers were systematically investigated by adjusting acid kinds, concentration, the ratio of APS/An, the mounts of TPA and PPDA. The crosslinked PANI displayed a conductivity increase of up to 25% compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 23 publications
2
33
0
Order By: Relevance
“…It should be noted that the electrical properties of PA NI-ICE were largely depending on the synthesis temperature,w here three orders of magnitude lower current flows were attained at subzero temperature conditions (Supporting Information, Figure S2). Because it is well-known that the key parameters affecting electrical conductivities of conducting polymers are conjugation length [11] and doping level, [12] molecular characteristics of PA NI-ICE were examined in comparison to PA NI-ED.A s shown in the Supporting Information, Figure S4, from the UV/Vis and IR absorption spectra, essentially the same conjugation length and doping level were identified for PA NI-ICE and PA NI-ED.W ethus deduce that the improvement in the electrical conductivity of PA NI-ICE did not originate from chemical factors. [30] The I-V curve of graphene synthesized by chemical vapor deposition (graphene-CVD,s heet resistance of ca.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the electrical properties of PA NI-ICE were largely depending on the synthesis temperature,w here three orders of magnitude lower current flows were attained at subzero temperature conditions (Supporting Information, Figure S2). Because it is well-known that the key parameters affecting electrical conductivities of conducting polymers are conjugation length [11] and doping level, [12] molecular characteristics of PA NI-ICE were examined in comparison to PA NI-ED.A s shown in the Supporting Information, Figure S4, from the UV/Vis and IR absorption spectra, essentially the same conjugation length and doping level were identified for PA NI-ICE and PA NI-ED.W ethus deduce that the improvement in the electrical conductivity of PA NI-ICE did not originate from chemical factors. [30] The I-V curve of graphene synthesized by chemical vapor deposition (graphene-CVD,s heet resistance of ca.…”
Section: Methodsmentioning
confidence: 99%
“…[2] Among av ariety of conducting polymers,P ANI has long been considered ap romising candidate for microelectronics and battery electrodes because of its high electrical conductivity,f acile wet chemical synthesis at low cost, easy doping process,a nd good environmental stability. [10] PA NI in the emeraldine salt form demonstrated ah igh electrical conductivity ranging from 10 À3 to 10 2 Scm À1 with varying conjugation length, [11] doping level, [12] and the type of dopant. [13] Decades of research on PA NI have further revealed that the electrical properties of PA NI can be largely tailored by changing the dimensionality of nanostructures.…”
mentioning
confidence: 99%
“…25,36 The proton transfer between polymer and water molecules as well as delocalization of the dopant ions with water ingress promotes the intra- chain conduction, while the swelling phenomenon could possibly impede the interchain conduction (Fig. The intrachain conduction depends on some factors such as frequency of defect sites and extent of conjugation, whereas the interchain conduction depends on the presence of conjugated cross-links between the chains, the closeness of different chains, and their orientation relative to each other.…”
Section: Humidity Sensing Performancementioning
confidence: 99%
“…Among a variety of conducting polymers, PANI has long been considered a promising candidate for microelectronics and battery electrodes because of its high electrical conductivity, facile wet chemical synthesis at low cost, easy doping process, and good environmental stability 10. PANI in the emeraldine salt form demonstrated a high electrical conductivity ranging from 10 −3 to 10 2 S cm −1 with varying conjugation length,11 doping level,12 and the type of dopant 13. Decades of research on PANI have further revealed that the electrical properties of PANI can be largely tailored by changing the dimensionality of nanostructures 14…”
Section: Methodsmentioning
confidence: 99%